Exosomal miR-183-5p Shuttled by M2 Polarized Tumor-Associated Macrophage Promotes the Development of Colon Cancer via Targeting THEM4 Mediated PI3K/AKT and NF-κB Pathways - Zhang, Shangxin; Li, Deguan; Zhao, Min; Yang, Fei; Sang, Changye; Yan, Changhong; Wang, Zhenjun; Li, Yongxiang (Frontiers in Oncology, 2021)
Background: Abnormal accumulation of macrophages in the colon cancer (CC) contribute to its progression. miR-183-5p has been confirmed as an oncogene in CC and this article explores the effect and mechanism of exosomal miR-183-5p enriched by M2-polarized tumor-associated macrophages (TAM) on CC cells. Methods: The human macrophage THP1 was induced to M2 polarization through IL-4 and IL-13 treatment. Exosomes in THP1 were isolated through ultracentrifugation, and the miR-183-5p expression in macrophages and exosomes was verified by quantitative reverse transcription-polymerase chain reaction (qRT-PCR). The miR-183-5p inhibitors and mimics were applied to down-regulate and upregulate miR-183-5p in macrophages, respectively. Meanwhile, CC cell lines LoVo and SW480 were treated with the macrophage conditioned medium and exosomes, respectively. CC cells’ proliferation, invasion, and apoptosis were tested by the cell counting kit-8 (CCK-8) assay, colony formation assay, flow cytometry (FCM), Transwell assay, and xenograft assay, respectively. The profiles of thioesterase superfamily member 4 (THEM4), Akt, and NF-κB were compared by Western blotting (WB). Results: The miR-183-5p level in M2-TAM and M2-TAM-derived exosomes was significantly increased. Meanwhile, M2-TAM and M2-TAM-derived exosomes significantly facilitated CC cell proliferation and invasion and dampened apoptosis. Overexpression of miR-183-5p in M2-TAM aggravated M2-TAM-mediated promotive effects on CC cells, with down-regulating miR-183-5p reversed M2-TAM-mediated tumor-promotive effects. Mechanically, miR-183-5p targeted THEM4 and inhibited its mRNA and protein expression. Overexpressing THEM4 abated miR-183-5p-mediated carcinogenic effects and inactivates Akt and NF-κB pathways in CC cells. Overall, this article elaborated that exosomal miR-183-5p shuttled by M2-TAM mediated Akt/NF-κB pathway to accelerate CC progression through targeting THEM4.